THEMATIC MEASURES FOR REDUCING POST-HARVEST LOSSES OF VEGETABLE CROPS AMONG FARMERS IN BENUE STATE, NIGERIA - EN, MBAH; NE, AMAH; MN, OKEKE (Innovare Journal of Agricultural Sciences, 2022)
The survey was carried out to ascertain thematic measures for reducing post-harvest losses of vegetable crops among farmers in Benue State, Nigeria. Questionnaire was used to collect data from a sample of 96 respondents used for the study. Data were analyzed using frequency, percentage, mean score, and standard deviation. Findings of the study revealed that about 57% of the respondents were females while 42.7% were males, 46.9% of the respondents were aged 31–40 years, and majority (80.2%) were married with 75.0% of the respondents having farming as a major occupation. A greater percentage (78.1%) of the respondents had between 6 and 10 years of farming experience and mean household size of about six persons. Results show effects of post-harvest losses to include reduction in income generation (M=3.80), decrease in quality of produce (M=3.66), unstable supply of produce (M=3.39), high cost of vegetable (M=3.30), decrease in nutritional content of the produce (M=3.26), loss of investment made by the farmer (M=3.25), and reduction on availability of vegetables for household consumption (M=3.24). Adequate provision of storage facilities (M=3.85), proper cleaning of produce (M=3.65), proper packaging of produce (M=3.60), adequate transportation facilities (M=3.56), sale of produce immediately after harvest (M=3.45), and harvesting at the right time (M=3.45) were measures indicated by the respondents for reducing post-harvest losses of vegetable crops. The study therefore recommends that there is a need for provision of adequate storage facilities to prevent losses of vegetable crops after harvesting. It also highlights that good sanitation practices in all post-harvest operations are very important factors in eliminating sources of infection and reducing contamination.